The neuroscience of sleep and dreams - McNamara, Patrick 1956- (Cambridge University Press, 2019)
This book provides a complete introduction to the neuroscience of sleep and dreams in plain language. In it, Patrick McNamara outlines new discoveries in the science of sleep and dreams, places them within an evolutionary context, and brings them together with existing scientific findings and implications for sleep medicine. Unlike other introductory texts, the important evolutionary background and social nature of sleep and dreams is emphasized. Major advances in sleep medicine, sleep and memory, dream content analyzes, brain correlates of sleep stages and lifespan development of sleep are covered in depth. While the text is geared towards students, the general reader and scientists studying other disciplines will find it accessible and informative.